ORGANIZATION OF STUDENTS’ INDIVIDUAL WORK IN THE STUDY OF HUMAN ANATOMY - Жураківська, О.Я. (World of Medicine and Biology, 2015)
Student’s individual work is one of the main forms of educational process in a credit-module system and is aimed to develop the personality of future specialist, to form a creative student, who can either acquire knowledge himself or realize information according to nowadays practical demands. Different forms of class and extracurricular individual work are used at the Department of Human Anatomy, Operative Surgery and Topographic Anatomy of SHEE "Ivano-Frankivsk National Medical University". The correct organization of individual work provides a complete mastering of program material at human anatomy, appropriate practical skills, getting additional scientific information and encourages students to self-education. The effectiveness of individual work depends on modern methodical forms and methods of their realization on the background of systematic academic and self-control.
Keywords: students’ individual work; human anatomy; students’ scientific workshop